The contingent effect of incarceration on state health outcomes - Christopher Uggen; Jason Schnittker; Sarah Shannon; Michael Massoglia (Elsevier, 2023)
Introduction: This study examines how growth in the population of former prisoners affects rates of communicable diseases such as tuberculosis, syphilis, chlamydia, and HIV. Methods: We estimate state-level fixed effects count models showing how the former prisoner population affected communicable disease in U.S. states from 1987 to 2010, a period of dramatic growth in incarceration. Results: We find contingent effects, based on how specific diseases are recognized, tested, and treated in prisons. The rate of former prisoners increases diseases that are poorly addressed in the prison health care system (e.g., chlamydia), but decreases diseases that are routinely tested and treated (e.g., tuberculosis). For HIV, the relationship has shifted in response to specific treatment mandates and protocols. Data on prison healthcare spending tracks these contingencies. Discussion: Improving the health of prisoners can improve the health of the communities to which they return. We consider these results in light of the relative quality of detection and treatment available to underserved populations within and outside prisons.